The Implementation of Inquiry Learning Model to Improve Students’ Achievement in English Lesson - Ayuna Olenta (Indonesian Journal of Integrated English Language Teaching, 2018)
Language becomes one of the skills needed to achieve success. The global language that becomes an important skill is English. The ideal English skills can be achieved through the process of learning at schools through English subjects that becomes the main goal of learning outcomes. Based on preliminary observations conducted by the researcher in class X IPS 2 SMA Negeri 5 Pekanbaru, there were some problems and conditions such as: 1) less effective and efficient learning process, 2) low student activity level, 3) student creativity level low, 4) students are often wrong in pronunciation, 5) learners often do activities related outside learning. This phenomenon that causes learning English in the class is not conducive, effective and efficient and impact on low learning outcomes and do not reach the minimum criteria that have been established defined 72. Needed a solution in improving learning outcomes is through the application of learning models. Strategy that can be applied as a learning solution that is by applying Inquiry learning model. This learning model can involve students actively, critically and creatively in learning. This class action research was conducted in class X IPS 2 SMA Negeri 5 Pekanbaru. Technique of collecting data that is done is test and observation. The method used was Classroom Action Research by doing two cycles in the implementation. Based on the results of classroom action research found that the students' learning mastery in cycle I showed that the activities of learners at each meeting for cycle 1 have increased. An increase in the percentage of learners who got the completeness with a score of 76 resulted in an average grade increase from 72 at baseline to 75. The results of the second cycle test showed that all learners who scored ≥ 76 or completed with 100% percentage with average classical that is 89. Application of Inquiry learning model can influence and improve result and mastery learners learn.